Candidate gene linkage analysis indicates genetic heterogeneity in Marfan syndrome - Teixeira,L.V.S. (2011)
Marfan syndrome (MFS) is an autosomal dominant disease of the connective tissue that affects the ocular, skeletal and cardiovascular systems, with a wide clinical variability. Although mutations in the FBN1 gene have been recognized as the cause of the disease, more recently other loci have been associated with MFS, indicating the genetic heterogeneity of this disease. We addressed the issue of genetic heterogeneity in MFS by performing linkage analysis of the FBN1 and TGFBR2 genes in 34 families (345 subjects) who met the clinical diagnostic criteria for the disease according to Ghent. Using a total of six microsatellite markers, we found that linkage with the FBN1 gene was observed or not excluded in 70.6% (24/34) of the families, and in 1 family the MFS phenotype segregated with the TGFBR2 gene. Moreover, in 4 families linkage with the FBN1 and TGFBR2 genes was excluded, and no mutations were identified in the coding region of TGFBR1, indicating the existence of other genes involved in MFS. Our results suggest that the genetic heterogeneity of MFS may be greater that previously reported.